Research on the evaluation and optimization of the effect of rural education poverty alleviation: Based on the field survey in Youyang County, Chongqing, China - Zhang, Dan; Liu, Jianyin (Nurture, 2023)
Purpose: This study explores the effect of education poverty alleviation policy under the precise poverty alleviation model, aiming to provide decision-making suggestions for relative poverty governance and risk prevention of returning to poverty. Design/Methodology/Approach: Using the methods of investigation, statistical analysis and institutional analysis, this paper explores the effect and optimization path of educational poverty alleviation in Youyang County, Chongqing. Findings: Rural poor households primarily benefit from government policies on education, as well as subsidies and allowances for students, in their efforts to alleviate educational poverty. However, these households may lack awareness of their own potential for skills training and employment conversion. Additionally, satisfaction with educational poverty alleviation efforts varies among rural households with differing income sources, education levels, and types of poverty. The most desired improvements in educational poverty alleviation among rural poor households include enhancing teaching quality, increasing educational awareness, reducing educational costs, and promoting compulsory education. Conclusion: From the perspective of poor households’ perception, this paper systematically reveals the performance characteristics and needs identification of educational poverty alleviation, and then puts forward policy suggestions for optimizing the performance of educational poverty alleviation. Research Limitations/Implications: Due to time and funding constraints, the number of research samples for this paper needs to be increased to improve the universality of the research conclusions. Practical Implications: The research findings can provide theoretical and practical references for exploring education to block the inter-generational transmission of poverty and scientifically designing educational poverty alleviation policies. Contribution to Literature: It enriches and expands the evaluation perspective, index system, and optimization path of the effect of education poverty alleviation policy.